Personal, partner and public health benefits of testing for Chlamydia trachomatis infections in women - Bruisten, Sylvia M. (Journal of Laboratory and Precision Medicine; Vol 2 (August 2017): Journal of Laboratory and Precision Medicine, 2017)
In view of personalised laboratory testing for the presence of infections with Chlamydia trachomatis the paper by Wiesenfeld fits perfectly (1). The paper starts with a case of a 19-year-old woman visiting her physician for preventive reasons. She is sexually active and has no complaints. The question is raised whether she should be screened for Chlamydia trachomatis. The answer is yes and Wiesenfeld gives a number of good arguments why women at the reproductive age or others at increased risk for infection should be (regularly) tested.